2021
DOI: 10.1016/j.bpj.2021.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent dynamics of rupture transitions of giant lipid vesicles at solid surfaces

Abstract: Single giant vesicles (GVs) rupture spontaneously from their salt-laden suspension onto solid surfaces. At hydrophilic surfaces, they rupture via a recurrent burst-heal dynamics: during burst, single pores nucleate at the contact boundary of the adhering vesicles facilitating asymmetric spreading and producing a "heart" shaped membrane patch. During the healing phase, the competing pore closure produces a daughter vesicle.At hydrophobic surfaces, by contrast, the GVs rupture via a distinctly different, yet rec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 77 publications
(77 reference statements)
2
14
0
Order By: Relevance
“…Later, the rupture dynamics of GUVs caused by interaction with hydrophobic and hydrophilic surfaces on a glass substrate were investigated. 99 For the hydrophobic surface, a pore was first initiated and then closed by expelling internal fluid, which resulted in a smaller vesicle than the original one. The lipid molecules of the inner and outer monolayer exchanged positions in the smaller vesicle, leaving a lipid monolayer on the hydrophobic surface.…”
Section: Resultsmentioning
confidence: 99%
“…Later, the rupture dynamics of GUVs caused by interaction with hydrophobic and hydrophilic surfaces on a glass substrate were investigated. 99 For the hydrophobic surface, a pore was first initiated and then closed by expelling internal fluid, which resulted in a smaller vesicle than the original one. The lipid molecules of the inner and outer monolayer exchanged positions in the smaller vesicle, leaving a lipid monolayer on the hydrophobic surface.…”
Section: Resultsmentioning
confidence: 99%
“…This mechanism stands in contrast to indications in the literature that outright LPS capture occurs [45]. Both theoretical and experimental research has confirmed that the disintegration of micelles and vesicles is possible at the solid-liquid interface and that there is a dependence on the free energy properties of the solid surface under study [46][47][48]. It would clearly be anticipated, in this case, that the presence of PMB would enhance this process.…”
Section: Free and Bound Lps On Interaction With Pmb-modified Glass Beadsmentioning
confidence: 62%
“…The fusion of lipid vesicles has been explored in detail for a range of substrates. 22 , 23 , 41 43 We find that while the fusion of PGUVs proceeds in a similar fashion, there are some important differences. LGUVs fused instantaneously on hydrophilic glass and PDMS substrates using iso-osmotic buffer.…”
Section: Results and Discussionmentioning
confidence: 77%
“…Polymer GUVs appear to fuse onto glass and PDMS substrates via a single-burst event, in contrast to lipid GUVs, which often fuse in a cascade fashion 43 ( Figure S1 , Supporting Videos S1 and S2 ). This results in large polymer patches of distinct heart or circular shapes, with a low density of remaining daughter vesicles or other visible defects ( Figure 1 ).…”
Section: Results and Discussionmentioning
confidence: 99%